2014
DOI: 10.1136/heartjnl-2013-305303
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stroke or TIA in patients without atrial fibrillation using CHADS2and CHA2DS2-VASc scores

Abstract: In patients with ACS but no AF, the CHADS2 and CHA2DS2-VASc scores predict ischaemic stroke/TIA events with similar accuracy to that observed in historical populations with non-valvular AF, but with lower absolute event rates. Further study of the utility of the CHADS2 and CHA2DS2-VASc scores for the assessment of thromboembolic risk and selection of antithrombotic therapy in patients without AF is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
95
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 31 publications
11
95
0
3
Order By: Relevance
“…The CHA 2 DS 2 ‐VASc score has been proved to be more sensitive than the CHADS 2 score to predict cardio‐embolic events in AF patients 7. In recent years, the use of the CHA 2 DS 2 ‐VASc score in predicting ischemic stroke, thromboembolism, and death has extended beyond the originally proposed AF field 8, 9. It has been reported that high CHA 2 DS 2 ‐VASc score are associated with mortality in patients with acute coronary syndrome,10 irrespective of the presence or absence of AF.…”
Section: Introductionmentioning
confidence: 99%
“…The CHA 2 DS 2 ‐VASc score has been proved to be more sensitive than the CHADS 2 score to predict cardio‐embolic events in AF patients 7. In recent years, the use of the CHA 2 DS 2 ‐VASc score in predicting ischemic stroke, thromboembolism, and death has extended beyond the originally proposed AF field 8, 9. It has been reported that high CHA 2 DS 2 ‐VASc score are associated with mortality in patients with acute coronary syndrome,10 irrespective of the presence or absence of AF.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 These clinical tools have predictive capacity for adverse outcomes even in patients without known AF, including the risk of death after stroke, the risk of incident AF, and the risk of stroke in unselected patients, in patients with stable coronary artery or after an acute coronary syndrome. [11][12][13][14][15][16] A better identification of the risk of incident AF in patients with ischemic stroke is currently a challenge. We aimed to identify patients with ischemic stroke without prior diagnosed AF who are at higher risk of developing or having a subsequent diagnosis of incident AF based on multiple risk factors.…”
mentioning
confidence: 99%
“…ischaemic attack (TIA) in the absence of AF in patients with an acute coronary syndrome (ACS). 36 Both these scores showed a reasonable association predicted annual risk of stroke/TIA with an absolute annual incidence of 1% with CHADS 2 ≥3 and CHA 2 DS 2 Vasc ≥4. This is in line with the results from another study by Poci et al 37 that found association of CHADS s with mortality and stroke.…”
Section: Epidemiology and Risk Factors Increasing Incidence Of Af In mentioning
confidence: 99%